2020
DOI: 10.3389/fcell.2020.00237
|View full text |Cite
|
Sign up to set email alerts
|

Site-Dependent Lineage Preference of Adipose Stem Cells

Abstract: Adult stem cells have unique properties in both proliferation and differentiation preference. In this study, we hypothesized that adipose stem cells have a depotdependent lineage preference. Four rabbits were used to provide donor-matched adipose stem cells from either subcutaneous adipose tissue (ScAT) or infrapatellar fat pad (IPFP). Proliferation and multi-lineage differentiation were evaluated in adipose stem cells from donor-matched ScAT and IPFP. RNA sequencing (RNA-seq) and proteomics were conducted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 89 publications
0
12
0
Order By: Relevance
“…It is known that ASCs, which are mesenchymal stem cells not yet committed to the adipocyte lineage, have the ability to differentiate into multiple cell lineages, including adipocytes (white or brown) and endothelial cells [ 70 , 71 , 72 , 73 ]. There has been previous histological evidence to suggest that adipocytes and adipose-derived endothelial cells share a common ancestor residing in the vascular niche [ 34 , 74 , 75 ].…”
Section: Cellular Crosstalk and Paracrine Signaling During Simultaneo...mentioning
confidence: 99%
“…It is known that ASCs, which are mesenchymal stem cells not yet committed to the adipocyte lineage, have the ability to differentiate into multiple cell lineages, including adipocytes (white or brown) and endothelial cells [ 70 , 71 , 72 , 73 ]. There has been previous histological evidence to suggest that adipocytes and adipose-derived endothelial cells share a common ancestor residing in the vascular niche [ 34 , 74 , 75 ].…”
Section: Cellular Crosstalk and Paracrine Signaling During Simultaneo...mentioning
confidence: 99%
“…Infrapatellar fat pads from four New Zealand White (NZW) rabbits were used to collect stem cells (IPFSCs) after a sequential digestion using 0.1% trypsin (Roche, Indianapolis, IN) for 30 min and 0.1% collagenase P (Roche) for 2 h to release cells. The stemness of IPFSCs was characterized in both human (He and Pei, 2013;Pizzute et al, 2016;Wang et al, 2019;Wang Y. M. et al, 2020) and rabbit donors (Wang T. et al, 2020). The pooled IPFSCs were cultured in growth medium [Minimum Essential Medium-Alpha Modification (αMEM) containing 10% fetal bovine serum (FBS), 100 U/mL penicillin, 100 µg/mL streptomycin, and 0.25 µg/mL fungizone (Invitrogen, Carlsbad, CA)] at 37 • C in a humidified 21% O 2 and 5% CO 2 incubator.…”
Section: Ipfsc Isolation and Culturementioning
confidence: 99%
“…Increasing data indicate the advantages of infrapatellar fat pad (IPFP)-derived stem cells (IPFSCs) as a stem cell source due to strong proliferation capacities and multilineage differentiation potentials, particularly for cartilage engineering and regeneration (Sun et al, 2018;Wang T. et al, 2020). Among the candidate scaffold materials, polylactic-co-glycolic acid (PLGA) is one of the most widely used biodegradable polymers, owing to its prominent advantages such as maneuverability of degradation rates and outstanding processability (Uematsu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…As a thin tissue (2–3 cell layers) lining the joints, however, a limited number of cells can be isolated from a synovial tissue biopsy through arthroscopy and harvested synovial tissue is often contaminated with sub-synovial connective tissue. Recent studies demonstrated that infrapatellar fat pad (IPFP)-derived stem cells (IPFSCs) can be used as an alternative stem cell source due to their strong chondrogenic potential and the spontaneous self-healing ability of IPFP [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our recent report assessed human SDSCs' proliferation and chondrogenic capacity after expansion on dECMs from different human cell types, including SDSCs (SECM), adipose-derived stem cells (ADSCs) (AECM), urine-derived stem cells (UDSCs) (UECM), and dermal fibroblasts (DFs) (DECM), with tissue culture plastic (Plastic) as a substrate control [ 16 ]. Given that tissue-specific stem cells are significantly influenced by the tissue-specific matrix microenvironment they harbor [ 2 ], our initial expectation was that SDSCs grown on SECM could exhibit the greatest chondrogenic potential compared to the Plastic group (non-dECM control) and other dECM control groups including AECM (deposited by ADSCs with limited chondrogenic capacity) [ 4 , 5 ], UECM (deposited by UDSCs without chondrogenic capacity) [ 17 ], and DECM (deposited by DFs which are not stem cells). However, we found that human SDSCs exhibited the greatest proliferation and chondrogenic capacity when grown on UECM, followed by those grown on AECM and DECM, with those grown on SECM being the last; all C-dECM groups had superior performance compared to the Plastic group.…”
Section: Introductionmentioning
confidence: 99%